The 7x4 field: the seven categories for reasons behind sleeping prob-lems, and the four cornerstones of a healthy life. - Heiska, Juhani (IJRDO - Journal of Social Science and Humanities Research, 2020)
Each year there are numerous scientific publications about sleeping problems. Utilising this information to prevent mental problems and disorders, as well as abnormal negative behaviour, practically calls for a functional method of categorisation. A 7x4 field for this precise purpose has been in development in Finland since the 1980s. This article explores this field’s applicability in tackling sleeping problems. The study in question utilised a multitude of research reports on sleeping problems and placed them within the 7x4 field. According to the results, sleeping problems can be assigned to seven major categories. The four cornerstones of well-being included in the 7x4 field also bring structure to the enormous amount of data and serve the purposes of preventative measures.